2017
DOI: 10.1088/1361-6668/aa570b
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic shielding for superconducting RF cavities

Abstract: Magnetic shielding is a key technology for superconducting radio frequency (RF) cavities. There are basically two approaches for shielding: (1) surround the cavity of interest with high permeability material and divert magnetic flux around it (passive shielding); and (2) create a magnetic field using coils that cancels the ambient magnetic field in the area of interest (active shielding). The choice of approach depends on the magnitude of the ambient magnetic field, residual magnetic field tolerance, shape of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…According to the magnetic field before and after shielding, the SF reaches up to 99.9%. It is better than cylindrical superconducting RF cavity shield, whose residual magnetic field is 100 nT [20]. When the electromagnetic environment is relatively stable in the evening, the magnetic field in the shielding system is smaller and more stable, which ensures the operation of the precision magnetic measuring instruments.…”
Section: Evaluation Of Shield Factormentioning
confidence: 99%
“…According to the magnetic field before and after shielding, the SF reaches up to 99.9%. It is better than cylindrical superconducting RF cavity shield, whose residual magnetic field is 100 nT [20]. When the electromagnetic environment is relatively stable in the evening, the magnetic field in the shielding system is smaller and more stable, which ensures the operation of the precision magnetic measuring instruments.…”
Section: Evaluation Of Shield Factormentioning
confidence: 99%
“…of neutral antimatter. Masuzawa [14] measured the permeabilities of various shielding materials at a temperature of 4 K for magnetic shielding of superconducting radio frequency cavities. It can be concluded that the shielding materials for cryogenic systems are usually low-temperature high permeability materials and superconducting materials.…”
Section: Jinst 16 P04007mentioning
confidence: 99%
“…A magnetic shield is used to prevent magnetic flux trapping. Studies of potential magnetic shields for ILC SRF cavities are presented in [12][13][14].…”
Section: Magnetic Shielding In Linear Collidersmentioning
confidence: 99%
“…It was observed in [13,38] that the shielding factor of a mu-metal shield degrades at very low (superconducting) temperatures. This is only a concern for accelerators that operate at superconducting temperatures, such as the ILC.…”
Section: Temperaturementioning
confidence: 99%